The new basics : education and the future of work in the Telematic Age - Thornburg, David D. (Association for Supervision and Curriculum Development, 2002)
The increasing globalization of work--coupled with rapid advancements in communications technology--is making age-old teaching methods irrelevant. To thrive in the plugged-in future workplace, students today need to learn a whole new set of fundamental skills. According to David Thornburg, we are on the cusp of a completely new era. The conventions of interoffice hierarchies, deskbound workers, and long-term employment contracts will quickly give way to a "telematic" model of work, in which workers are free to hop from client to client and country to country at the speed of a DSL connection. Today's curriculum is predicated on yesterday's realities, and must be reexamined to better reflect the digital age. This book explores . The foundations of the future economy, . The characteristics needed to succeed in the emerging world, and . The changes we need to make in education to ensure that all students leave school prepared to face the challenges of a redefined world. The New Basics: Education and the Future of Work in the Telematic Age provides an in-depth discussion of the skills necessary for professional success in the coming years, along with strategies on how best to teach them in the classroom. Filled to capacity with visionary observations, practical suggestions for innovative instruction, and engaging discussions of the historical precedents for remodeled curriculum, this book is essential for those seeking to address the pressing issues of the new millennium